Reasons for disengagement in first-episode psychosis – perspectives from service users and their caregivers - Yi Chian Chua; Kumarasan Roystonn; K. Pushpa; Swapna Verma; Charmaine Tang (BMC Psychiatry)
Abstract Background The efforts of early psychosis intervention programmes can be impeded by difficulties in maintaining the engagement of service users. As disengagement is often an autonomous decision made by service users, the main aim of this study was to gain insight into the reasons for service user disengagement through qualitative interviews with the service users themselves, and caregivers as proxies or secondary informants. Methods Participants recruited for the study were enrolled in the Early Psychosis Intervention Programme in Singapore for at least a year, aged 21 and above, able to communicate in English, and had disengaged for at least three months. The recruitment and interview processes were conducted independently for service user and caregiver participants. Potential participants were invited to a face-to-face semi-structured interview over video call or in-person. Each interview spanned one to two hours, and comprised five phases – icebreaker, exploration of the participant’s experience with EPIP before deciding to disengage, discussion of reasons for disengagement, exploration of the post-disengagement experience, and feedback and suggestions for EPIP. Recruitment aimed to conclude after 10–15 participants were interviewed for both service user and caregiver groups, with the expectation that data sufficiency would be reached with no new themes being generated. Results Ultimately, 12 service user and 12 caregiver participants were recruited. There were six pairs of service user and caregiver dyads, where the caregivers interviewed were caring for service users also enrolled in the study. Valuable qualitative insights were gathered, including the type of disengagement, medication compliance during disengagement, the decision-making process behind disengaging, and circumstances surrounding re-engagement. A total of five categories each with subthemes were identified from the reasons for service user disengagement – individual factors, stigma, progression, treatment factors, and external factors. Conclusions There is a need to narrow down urgent areas of attention, aligning the study themes with established risk factors so that feasible solutions can be developed and appropriate care models can be adopted, to minimise adverse outcomes related to disengagement. It is important to keep an open mind to understand what personal recovery means to the individual service user, so that treatment goals can be better harmonised.